Anti-Melanoma Activities of Artemisone and Prenylated Amino-Artemisinins in Combination With Known Anticancer Drugs - Wong, Ho Ning; Lewies, Angélique; Haigh, Michaela; Viljoen, Joe M.; Wentzel, Johannes F.; Haynes, Richard K.; du Plessis, Lissinda H. (Frontiers in Pharmacology, 2020)
The most frequently occurring cancers are those of the skin, with melanoma being the leading cause of death due to skin cancer. Breakthroughs in chemotherapy have been achieved in certain cases, though only marginal advances have been made in treatment of metastatic melanoma. Strategies aimed at inducing redox dysregulation by use of reactive oxygen species (ROS) inducers present a promising approach to cancer chemotherapy. Here we use a rational combination of an oxidant drug combined with a redox or pro-oxidant drug to optimize the cytotoxic effect. Thus we demonstrate for the first time enhanced activity of the amino-artemisinin artemisone and novel prenylated piperazine derivatives derived from dihydroartemisinin as the oxidant component, and elesclomol-Cu(II) as the redox component, against human malignant melanoma cells A375 in vitro. The combinations caused a dose dependent decrease in cell numbers and increase in apoptosis. The results indicate that oxidant-redox drug combinations have considerable potential and warrant further investigation.